O Programa Bolsa Família: Desenho institucional, impactos e possibilidades futuras - Sergei Soares; Natália Sátyro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This text discusses the Bolsa Família Program, its institutional design, implementation issues, its impacts and possibilities for future evolution. We discuss the institutional division of responsibilities, benefits, conditionalities and federative arrangements. With regards to implementation issues, we discuss the vitally important Single Registry of Beneficiaries, targeting, coverage and the discussion about exit strategies for beneficiary families. We also briefly review the literature on Bolsa Família`s impacts upon inequality, poverty, nutrition, labor supply, and political participation. We conclude that at present Bolsa Família is neither entirely a social protection program nor a program for the generation of opportunities. In the near future, a definition will be necessary because the two objectives are incompatible in a single program.
Keywords: I38; 330